(untitled) (Swiss Medical Weekly, 2025)
INTRODUCTION: Most European transplant centres require patients to abstain from alcohol consumption for at least 6 months to be listed for liver transplantation, even though delayed transplantation is associated with increased mortality. This study examined the effects of a shorter duration of alcohol abstinence before placement on the waiting list for liver transplantation on post-transplant survival and quality of life. This article contributes to the ongoing debate on whether patients with less than 6 months of alcohol abstinence should be categorically excluded from transplantation. METHODS: This retrospective cohort study analysed patients at the University Hospital Zurich who underwent liver transplantation for any indication between 2011 and 2019. Patients younger than 18 years and those with acute liver failure were excluded. The follow-up period was 3 years. The outcomes were post-transplant survival and quality of life in patients with less than (group 1) or more than (group 2) 6 months of abstinence before being listed for liver transplantation. Survival was compared using log-rank tests, and quality of life (scored from 0 to 100) was compared using multivariate ANOVA with repeated measures. RESULTS: Of the 206 included patients, 50 (24%) had abstained from alcohol for less than 6 months before being listed for liver transplantation (group 1). The cohort had a median (IQR) age at transplantation of 59 (53–64) years, and 155 (75%) were men. Three-year survival was similar in patients with less than or more than 6 months of alcohol abstinence before listing (76% [95% CI, 62%; 86%] vs 78% [95% CI, 70%; 83%]). No significant differences in quality-of-life scores were observed between groups (F(2,244) = 0.814, p = 0.435), and no significant changes in quality of life over time were found within each group (F(1,133) = 0.346, p = 0.557). The median (IQR) quality of life score at 36 months after transplantation was 80 (56–92) in patients with less than 6 months of abstinence before listing versus 78 (63-90) in those with more than 6 months of abstinence. CONCLUSION: Post-transplant survival and quality of life did not differ between patients with less than 6 months and those with more than 6 months of alcohol abstinence before being listed for liver transplantation. These findings suggest that the strict 6-month abstinence requirement for inclusion on the waiting list should be reconsidered to prevent patients from being denied access to life-saving transplantation solely because of a shorter abstinence duration.